Nivel de conocimiento en tributación y evasión de impuestos en los comerciantes del mercado central de la ciudad de Iquitos periodo 2023 - Perez De La Cruz, Shirley Kattya (2024)
This study is focused on tax knowledge and tax evasion, developed with a quantitative methodology and correlation level and non-experimental design, including 120 merchants as the study population, with the main objective of determining the relationship between the level of knowledge in taxation and tax evasion in merchants in the central market of the city of Iquitos period 2023. The research identified that knowledge in taxation has a good level at 43.48%, regular at 33.70% and bad at 22.83%. On the other hand, tax evasion is identified as adequate in 22.83%, regular in 43.48% and finally bad in 33.70%. Likewise, Spearman's Rho Correlation Coefficient is identified between tax knowledge and tax evasion, equal to Rho= -0.593 and Sig.=0.000, which is significant. In this sense, it is concluded that there is an indirect relationship between the level of knowledge in taxation and tax evasion in the merchants of the central market of the city of Iquitos period 2023. Therefore, having greater knowledge in taxation is expected that tax evasion is reduced.